(untitled) (Libya Journal of Geographical Studies, 2023)
The subject of the study revolves around the environmental issue according to the perspective of geopolitics by highlighting the international positions of the political actors towards the global environmental issue and the efforts exerted to reduce the repercussions of this issue and the impact of these positions and efforts on environmental issues in international forums, and therefore the focus was on the political dimension of environmental issues And its impact on international relations and the causes and results of those positions on international affairs. The environmental issue has not received sufficient attention until the present time to place it at the top of international concerns, except by international institutions that do not have the authority to compel and make decisions while the force is still capable of activating interest in this issue. ignoring its real dangers. And with the emergence of the branch of geopolitics due to the interest of political geographers in the struggle of global powers, its causes and results, and since the comprehensive vision is the most important characteristic of research in geopolitics, and this vision is an important dimension in addressing the environmental issue in the sense that it is a complex and overlapping issue, which gives an opportunity to study the environmental issue from several aspects. It reveals the future image of the environmental issue on the international political stage, as it has become a new and influential variable in international affairs, from the study of international power struggles according to this new variable.